2022
DOI: 10.21203/rs.3.rs-1617041/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inverse-design of high-dimensional quantum optical circuits in a complex medium

Abstract: Programmable optical circuits form a key part of quantum technologies today, ranging from transceivers for quantum communication to integrated photonic chips for quantum information processing. As the size of such circuits is increased, maintaining precise control over every individual component becomes challenging, leading to a reduction in the quality of the operations performed. In parallel, minor imperfections in circuit fabrication are amplified in this regime, dramatically inhibiting their performance. H… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…We use the top-down approach to describe the linear optical circuit as a transformation built from a cascade of optical mode mixers {U j } separated by phase shifters {P j }. In this approach, we embed a d-dimensional circuit T within these large complex mode-mixers U j with dimension n ≫ d. 5 A programmable circuit with depth L (the number of layers) is represented as:…”
Section: Inverse Design For Manipulating Entanglementmentioning
confidence: 99%
See 1 more Smart Citation
“…We use the top-down approach to describe the linear optical circuit as a transformation built from a cascade of optical mode mixers {U j } separated by phase shifters {P j }. In this approach, we embed a d-dimensional circuit T within these large complex mode-mixers U j with dimension n ≫ d. 5 A programmable circuit with depth L (the number of layers) is represented as:…”
Section: Inverse Design For Manipulating Entanglementmentioning
confidence: 99%
“…The mode-mixers are placed between reprogrammable phase planes, which are programmed using an inverse-design approach. 5 This allows us to encode any high-dimensional unitary by harnessing the large dimensionality of the mode-mixers as an additional resource. In this work, we implement this architecture by placing a multi-mode fiber (MMF) between a pair of spatial light modulators (SLMs) to program a general unitary transformation.…”
Section: Introductionmentioning
confidence: 99%
“…2)Service Design Principles The concept of service design follows certain principles and standards, but the conclusions given by different researchers on the principles of service design are different. The current service design principles that are more recognized in the industry are the five principles proposed by Mark and Jacob in 2011, including user-centeredness, collaborative innovation, orderliness, tangibility, and integrity (Goel et al, 2022). Then, in practical research, they found that the five principles were not enough to meet the industry requirements of service design, so they proposed new service design principles in 2018.…”
Section: Service Design 1)service Design Conceptmentioning
confidence: 99%
“…Inverse problems in electromagnetics, encompassing inverse source [1,2], inverse scattering [3][4][5][6], inverse design [7], and inverse synthesis [8] problems, have found widespread applications in various fields, including microwave imaging [9], radar tracking [10], breast cancer detecting [11], remote sensing [12], tomography [13], seismology [14], failure analysis [15], nondestructive evaluation [16], antenna design and pattern synthesis [17,18], nanoscale optical positioning [19], and integrated quantum photonics [20][21][22]. Among these, electromagnetic inverse scattering focuses on detecting, locating, shape finding, and material imaging of unknown objects using scattered fields and Maxwell's equations.…”
Section: Introductionmentioning
confidence: 99%